2019
DOI: 10.1016/j.fss.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Towards probabilistic partial metric spaces: Diagonals between distance distributions

Abstract: The quantale of distance distributions is of fundamental importance for understanding probabilistic metric spaces as enriched categories. Motivated by the categorical interpretation of partial metric spaces, we are led to investigate the quantaloid of diagonals between distance distributions, which is expected to establish the categorical foundation of probabilistic partial metric spaces. Observing that the quantale of distance distributions w.r.t. an arbitrary continuous t-norm is non-divisible, we precisely … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Chai also gave a research on probabilistic quasi-metric spaces from the enriched categorical point of view in [4]. Similar to the study of probabilistic quasi-metric spaces, He, Lai and Shen considered the categorical interpretation of fuzzy partial metric spaces in [14]. Following Lawvere and Bar's idea, Clementino, Hofmann and Tholen developed the theory of monoidal topology, and showed that many topological structures such as approach spaces, metric spaces, (quasi-)unform spaces and so on all can be viewed as lax algebras with respect to certain monads (see [5-8, 15, 17, 23]).…”
Section: Introductionmentioning
confidence: 99%
“…Chai also gave a research on probabilistic quasi-metric spaces from the enriched categorical point of view in [4]. Similar to the study of probabilistic quasi-metric spaces, He, Lai and Shen considered the categorical interpretation of fuzzy partial metric spaces in [14]. Following Lawvere and Bar's idea, Clementino, Hofmann and Tholen developed the theory of monoidal topology, and showed that many topological structures such as approach spaces, metric spaces, (quasi-)unform spaces and so on all can be viewed as lax algebras with respect to certain monads (see [5-8, 15, 17, 23]).…”
Section: Introductionmentioning
confidence: 99%
“…We note that (∆ + , ≤) satisfies this property [15], however (∆ + , ≤, * ) is in general not divisible, see [8]. Also, L being a value quantale [5] ensures the property, see [13].…”
Section: Categorical Propertiesmentioning
confidence: 95%
“…[43] provides a topological characterization of partial metric spaces. Fuzzy and probabilistic partial metric spaces are well-investigated too [68], [67], [37]. Our description of generalized partial metric spaces was based on the elegant presentation from [40], [64] of such spaces as quantaloid-enriched categories.…”
Section: Related Workmentioning
confidence: 99%